Social relations and mental ill-health among newly arrived refugees in Sweden: A cross-sectional study - Elisabeth Mangrio; Mathias Grahn; Slobodan Zdravkovic; Carin Cuadra (Public Library of Science (PLoS), 2022)
Background Previous research indicates that social relations have an impact on the well-being of refugees and that well-being is important for effective integration into the host country. Few studies in Sweden have, to the best of our knowledge, looked at the association between social relations and mental ill-health among newly arrived refugees. The aim is to investigate what effect social relations have on the mental health of newly arrived refugees in the south of Sweden. Methods A cross-sectional study was conducted in Scania, the southernmost county of Sweden, between February 2015 and February 2016. The study population consisted of newly arrived adult refugees speaking Dari or Arabic, who received the civic and health information that is part of an introduction course for all newly arrived refugees. Results Individuals who rarely met with friends had higher odds of experiencing mental ill-health [OR = 1.70, 95% CI, 1.03-2.82] than individuals who frequently spent time with friends. Furthermore, individuals who seldom attended social/community meetings or activities in an organisation or group, such as a sports association or another kind of association, a church, a mosque, or women's or men's meetings, had higher odds of mental ill-health (OR = 1.58, 1.1-2.28), compared to those who frequently did so. Conclusions The study suggests a link between spending time with friends, as well as engaging in social/community activities, and the mental health of newly arrived refugees in the southernmost county of Sweden, which is one of the counties in Sweden that received the highest number of refugees. The results are in line with a previous study on the same subject in Sweden.